Anatomical and Chemical Properties of Keruing Wood from Labanan Research Forest, East Kalimantan - Lystia M Dewi; Supartini Supartini (Masyarakat Peneliti Kayu Indonesia, 2017)
Understanding the basic properties of wood is essential for its appropriate and efficient utilization. Anatomical feature for many species of wood, as an important basic property of wood, remained incomplete and mostly limited to the genus level, especially for Dipterocarpaceae. In the present works, three keruing species i.e. (Dipterocarpus stellatus Vesque, Dipterocarpus glabrigemmatus P.S. Ashton, and Dipterocarpus pachyphyllus Meijer) were studied for their anatomical and chemical properties. Observation of the microscopic and macroscopic features of these woods was conducted. Suitability of the wood for pulp and paper raw material was also assessed through fiber dimension measurement. Chemical component analyses were carried out based on appropriate Technical Association of the Pulp and Paper Industries (TAPPI) standard procedures. The result showed that in general, all species have resemblance in both anatomical and chemical properties. Even though, the lignin and extractives content of the three Dipterocarpus spp. were considered high, their fiber were classified as class I fiber quality; and thus very suitable for the raw material of pulp and paper production.Keywords: anatomical properties, chemical properties, Dipterocarpus spp., fibre quality, keruing